Meditation and Mindfulness in the Management of Fibromyalgia Syndrome - Biernacka, Martyna; Bieniasz, Anna; Agopsowicz, Katarzyna; Blicharz, Katarzyna; Biernacki, Igor; Bąk, Aleksandra; Mojżesz, Piotr; Zdziebło, Katarzyna; Sitko, Maria; Piwowar, Michalina (Quality in Sport, 2025)
Fibromyalgia is a complex and chronic pain syndrome characterized by widespread musculoskeletal pain, fatigue, sleep disturbances, hypersensitivity to stimuli, and frequently co-occurring psychological symptoms such as depression and anxiety. Although conventional treatments remain essential, their limited effectiveness combined with the multifaceted nature of fibromyalgia, often leads patients to explore complementary approaches and encourages a holistic management strategy for the disease. This review includes studies from the last 15 years, sourced from PubMed database, that focus on the role of meditation - particularly mindfulness-based practices, as a non-pharmacological intervention in the management of fibromyalgia. A growing body of evidence suggests that techniques incorporating meditation, such as mindfulness, Qigong, yoga, and conscious breathing can reduce pain intensity, improve sleep quality, and alleviate psychological distress. Meditation may also enhance emotional resilience and support self-regulation, offering patients a sense of agency in coping with chronic symptoms. Importantly, some studies indicate that mindfulness-based interventions are not only clinically beneficial but also cost-effective, by reducing reliance on healthcare resources. While methodological limitations remain present in much of the research, meditation-based therapies emerge as a promising and accessible complement to conventional fibromyalgia treatments, supporting a more holistic and patient-centered model of care.